2012
DOI: 10.1590/s1679-87592012000100002
|View full text |Cite
|
Sign up to set email alerts
|

Circulation and salt intrusion in the Piaçaguera Channel, Santos (SP)

Abstract: Analysis of thermohaline properties and currents sampled at an anchor station in the Piaçaguera Channel (Santos Estuary) in the austral winter was made in terms of tidal (neap and spring tidal cycles) and non-tidal conditions, with the objective to characterize the stratification, circulation and salt transport due to the fortnightly tidal modulation. Classical methods of observational data analysis of hourly and nearly synoptic observations and analytical simulations of nearly steady-state salinity and longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
9
0
5
Order By: Relevance
“…In general, the flood-ebb asymmetry in current was more significant during the spring tide, while stratification and shear intensification/relaxation were dependent on the tidal currents, leading to maximum stratification and shear during maximum flood currents, and not exceeding the maximum ebb currents (PARK; DAVES, 1990;MIRANDA et al, 2012). Potential explanations for the observed greater asymmetry during the sampled spring tidal condition were twofold.…”
Section: Hydrometeorological Propertiesmentioning
confidence: 93%
“…In general, the flood-ebb asymmetry in current was more significant during the spring tide, while stratification and shear intensification/relaxation were dependent on the tidal currents, leading to maximum stratification and shear during maximum flood currents, and not exceeding the maximum ebb currents (PARK; DAVES, 1990;MIRANDA et al, 2012). Potential explanations for the observed greater asymmetry during the sampled spring tidal condition were twofold.…”
Section: Hydrometeorological Propertiesmentioning
confidence: 93%
“…The estuarine system is characterized by a flat area surrounded by scarps of the plateau of Serra do Mar [1], and bordered by the cities of Santos, S. Vicente, Guarujá, Bertioga and Cubatão, which is one the most industrialized areas of South America [6]. The Santos estuary can be classified as a typical sub-tropical mangrove system, under significant anthropogenic pressure.…”
Section: Study Areamentioning
confidence: 99%
“…Santos harbor is the most important port in Brazil and the largest harbor in Latin America, which traded more than 110 million tons of cargo in the year 2018 [7]. The Santos estuary is a complex system whose geometry and river discharge has been drastically altered during the last century by urban and industrial development, land reclamation, dredging and effluent reception from multiple industries [6]. The estuary receives freshwater inflow from several small rivers that develop on the slopes of Serra do Mar, at heights of 700 meters [8].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that net salt flux is a balance of advection flux and a number of dispersive fluxes, including tide effect, shear effect and turbulence effect. The tidal effects are component of tidal sloshing, Stokes drift and cross-correlation between tide and salinity ( Kjerfve, 1986;Miranda et al, 2012;Restrepo and Kjerfve, 2002) . In steady-state, there is a balance between seaward advection of fluvial discharge and landward dispersion of saltier ocean water ( Hunkins, 1981;Miranda and Kjerfve, 1998;Siegle et al, 2009;Simpson et al, 1997;Uncles and Lewis, 2001) .…”
Section: Introductionmentioning
confidence: 99%